Avaliação de extratos de resíduos de lúpulos como clarificadores de cerveja - Melo, André da Silva Castilhos de (2020)
Beer is the beverage resulting from fermentation, from brewer's yeast, from malted barley or malt extract, previously submitted to a cooking process added with hops or hops extract, in which excess of turbidity and the presence of sediment are considered defects that compromise the quality of the drink. One way to minimize turbidity is the addition of clarifying agents, which act on the turbidity material (proteins and polyphenols). Thus, this work aimed to evaluate the clarifying power of hydroalcoholic extracts of american hops residues obtained from the process called "dry-hopping" as post-fermentation clarifiers in beer manufacturing. The proanthocyanidins from hops residues Citra, Ekuanot, Mosaic and Amarillo were quantified using ethanol/water solvent in different proportions (96, 75, 50 and 25% v/ v).For the evaluation of clarifiers, a beer called “American Pale Ale” was produced to which, on the ninth day of maturation/cold storage, commercial clarifying agents, carrageenan gum (Whirlfloc ®G), gelatin and silica gel (Spindasol ®SB3), in addition to hops extracts in a concentration of 3,49 milligrams of proanthocyanidins per liter of beer. To evaluate the clarification effect, the beer samples were subjected to analysis of protein content, total phenolic compounds, clarity, and turbidity. The 50/50% (v/v) ratio of ethanol/water solvent was the concentration that resulted in the greatest extraction of proanthocyanidins, reaching concentrations of 107,06; 364,52; 273,39 and 335,21mg/L, for Amarillo, Citra, Mosaic, and Ekuanot hops, respectively. After fermentation, the beer had 898,16 mg of proteins and 502 mg of total phenolic compounds per liter of beer. In the evaluation of beer in the stage of maturation/cold storage, after 5 days of the addition and action of hops extracts, a decrease in the levels of proteins and total phenolic compounds was observed. However, the intensity of the decrease varied depending on the type of hops, with Citra extract being the best performer. The clarifying agents, gelatin, Citra hops residue extract and the silica gel sol showed the lowest turbidity values (less than 6 EBC units -European Brewery Convention) after the stability test.In the sensory evaluation of clarified beer with Citra hops extract, the tasters reported a clear and shiny beer, within the standards for the “American Pale Ale” style. Thus, given the efficiency, Citra hops extract is suggested as a clarifying alternative to be used in the removal of proteins and polyphenols in the maturation/cold storage stage.